Income property valuation : principles and techniques of appraising income-producing real estate - Kinnard, William N. (Lexington, Mass. : Heath Lexington Books, 1971)
This book is directed toward the student of appraisal, with or without experience in the residential property field, who has little or no background in income property valuation.
Includes bibliographical references and index.
gp 22/01/2019
Loans
Keywords: Real property